Pemanfaatan Generative Artificial Intelligence Sebagai Mitra Belajar dalam Membangun Kemandirian Belajar Mahasiswa pada Mata Kuliah Konsep Dasar IPS SD - Eka Periaman Zai; Indah Wijaya Lase; Operianus Mendrofa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of Generative Artificial Intelligence (GenAI) presents new opportunities in higher education through its role as an adaptive learning partner. This study aims to explore the use of GenAI as a learning partner to support students' independent learning in the Basic Concepts of Elementary School Social Studies course. This study used a qualitative approach with a case study design in the Elementary School Teacher Education Study Program at Nias University. The research participants consisted of 16 students selected through purposive sampling techniques. Data were collected through observation, in-depth interviews, document analysis, and reflection journals, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that GenAI was used by students to understand concepts, explore ideas, obtain feedback, and reflect on learning. This utilization supports the formation of independent learning behavior through students' abilities to plan, implement, monitor, and evaluate their learning process. Optimizing the use of GenAI is influenced by digital literacy, the ability to create prompts, access to technology, and lecturer assistance in verifying information and maintaining academic ethics. This study shows that GenAI has the potential to support Self-Regulated Learning if it is pedagogically integrated as a learning partner, rather than as a substitute for the role of lecturers or students' thinking processes.